Diagnosis and Management of Hyperthyroidism in Pregnancy: A Review. Issue 11 (November 2016) - King, Jennifer Renae; Lachica, Ruben; Lee, Richard H.; Montoro, Martin; Mestman, Jorge
Abstract : Importance: Hyperthyroidism has important implications for pregnancy, affecting both mother and fetus. Appropriate maternal and fetal management iscritical to avoiding adverse pregnancy outcomes and requires a multidisciplinary approach. Objective: To describe maternal diagnosis and management of hyperthyroidism, across all stages of pregnancy. In addition, to review clinical signs of fetal thyroid dysfunction due to maternal Graves disease and discuss management considerations. Evidence Acquisition: Review of published articles on PubMed and guidelines by recognized governing organizations regarding the diagnostic and management considerations for hyperthyroidism in pregnancy, from preconception to the postpartum period. Results: Diagnosis of maternal hyperthyroidism involves both clinical symptoms and laboratory findings. Antithyroid medications are the mainstay of therapy, with trimester-specific pregnancy goals. Hyperthyroidism due to Graves disease has important diagnostic and management considerations for the fetus and neonate. Conclusions and Relevance: Hyperthyroidism in pregnancy affects mother, fetus, and neonate. Interpretation of thyroid tests and understanding the appropriate use of antithyroid drugs are fundamental. Proper education of physicians providing care to women with hyperthyroidism is essential and starts before pregnancy. Postpartum follow-up is an essential part of the care. A systematic approach to management will ensure optimal pregnancy outcomes. Target Audience: Obstetricians and gynecologists, family physicians Learning Objectives: After completing this activity, the learner should be better able to: (1) describe the diagnosis of hyperthyroidism in pregnancy, (2) discuss medical management of hyperthyroidism during pregnancy, (3) review the clinical signs of fetal thyroid dysfunction, (4) describe the symptoms and treatment of thyroid storm in pregnancy, and (5) review management considerations in the postpartum period for women with hyperthyroidism.